A novel method to measure biomechanical parameters of soccer kicks and two-footedness in the field - Attarzadeh, R.; Meamarbashi, A. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
There is some consensus that two-footed play is associated with skill in individual players. In sports biomeohanics, videography provided an indirect method for measuring kinematic parameters. However, these techniques are expensive, bulky and not portable. The current system is applicable in sports that involve high linear and relational kinematics and high impact contact with the ball. A novel sensor module mounted on a soccer shin guard and small data logger were previously designed and, validated (Meamarbashi, 2007). This design is able to record the linear and rotational movements in three axes as well as thigh linear kinematics at 200 Hz and save the data on a memory card. A custom PC Software was developed to measure the high kinematic parameters (linear and angular accelcrations and velocities) and compute the kinetic parameters (force, torque, angular momentum, impulse and angular power) of the instep kick and compare the right and left legs during trials of a subject or in the group. In this study, leg movement pattems of the subject legs investigated in compare to others. This novel technique is suitable in Soccer, Rugby, American Football, Tennis, etc to evaluate the player's right and left legs in the field.